RELASI SUAMI ISTERI ANTARA SYARAH UQUD AL-LUZZAI, KHI DAN PERTUKARAN PASAR - Fatawi, Fatawi (STAI Darul Qalam Tangerang, 2025)
This study examines Syarah Uqud al-Lujain by Sheikh Nawawi al-Bantani using a doctrinal legal approach and social change theory. The focus of the research is on the first and second chapters, which discuss the obligations of husbands and wives in building a harmonious family. In the modern context that emphasizes gender equality, the relevance of this text is often questioned. To address this, the study employs social exchange theory as the main framework, supported by the credo or shahada theory and the market price equilibrium theory. The research applies a library-based method with critical analysis of relevant literature. The findings indicate that although the book emerged within a patriarchal culture, its content does not contradict gender-friendly principles. Rather, it emphasizes reciprocal relations as an exchange of rights and obligations grounded in religious commitment, aiming to achieve equilibrium in family life